THE DEVELOPMENT OF INTERACTIVE E-BOOK MEDIA ON PROTIST TOPIC TO IMPROVE LEARNING OUTCOMES FOR 10TH GRADE OF SENIOR HIGH SCHOOL - Ferina Fatihah Sari; Widowati Budijastuti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Transformation in learning conditions during the pandemics makes students experience decreased learning achievement and difficulty absorbing new material. The government’s preventive efforts in tackling the learning process are by providing internet-based and technology-based learning. Therefore, interactive e-book media as a form of merging media in the form of the internet and technology is essential. This research aims to produce an interactive e-book media on protist topic to improve learning outcomes for 10th grade of senior high school that are valid, effective, and practical. This research is development research that refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The parameters measured were the validity of the interactive e-book media which was assessed based on the presentation, content, and language aspects by expert lecturers and biology teachers. The effectiveness of the interactive e-book media was obtained from the pretest and the posttest was analyzed using N-gain. The practicality of the interactive e-book media was obtained from the responses of twenty students in 10th grade of SMA Muhammadiyah 10 Gresik. The data obtained were analyzed descriptively quantitatively. The result showed that the interactive e-book media has an average percentage of validity score of 94.93%, with a very valid category. The effectiveness of the interactive e-book media obtained an average N-gain of 59, which is included in the medium category with a pretty effective interpretation. The practicality of the interactive e-book media obtained an average of percentage positive responses of 84.83% in the practical category. Based on these data, it could be concluded that the interactive e-book media on protist topic to improve learning outcomes for 10th grade of senior high school is very valid, pretty effective, and practical. This research showed that interactive e-book media gives significant impact on learning outcomes. Keywords: media, interactive E-book, Protist, learning outcomes